Intrusion detection system for various IoT attacks on MQTT protocol - Farhan; Mueth Ul Ehsan Ananno; Tanzil Talat Anonto; Sazzad Alam Tomal (Brac University, 2022)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2022.